A review of inorganic UV filters zinc oxide and titanium dioxide. Issue 6 (10th December 2018) - Schneider, Samantha L.; Lim, Henry W.
Summary: Photoprotection has become integral in the prevention of keratinocyte cancer and photoaging. Organic ultraviolet (UV) filters such as oxybenzone and octinoxate have become controversial due to their potential impact on the environmental and their potential human health risks. As such, inorganic UV filters, zinc oxide (ZnO) and titanium dioxide (TiO2 ), have become paramount in discussions about photoprotection. ZnO and TiO2 are used in sunscreens as nanoparticles, which denotes a size <100 nm. The smaller size of these mineral particles increases their cosmetic acceptability by users as they are much less visible after application. ZnO has a broad UVA‐UVB absorption curve, while TiO2 provides better UVB protection. Overall, the human health risks with inorganic filters are extremely low given a lack of percutaneous absorption; however, there is potential risk when exposed via inhalation, prompting recommendations against spray sunscreen products with nanoparticles. At this time, the known risk to the environment is low though the risk stratification may evolve with increasing usage of these filters and higher environmental concentrations. The continued practice of photoprotection is critical. The public should be counseled to seek shade, use photoprotective clothing including hats and glasses in addition to sunscreens on sun‐exposed skin. For those concerned about emerging evidence of environmental impact of organic UV filters, based on current evidence, ZnO and TiO2 ‐containing sunscreens are safe alternatives.